Hubungan Tingkat Pengetahuan Ibu dan Pola Makan Anak Dengan Status Gizi Anak - Utami, Sri; Nurhartanto, Adhi; Kustiani, Ai (CV. Rayyan Dwi Bharata, 2024)
Nutritional status is a picture of a person's body as a result of the food consumed in the body. Nutritional status can influence nutritional problems and nutritional problems can occur in all age groups. One factor that can influence a child's nutritional status is the mother's nutritional knowledge and eating patterns. A good diet can meet nutritional needs, while a poor diet can cause nutritional problems, such as undernutrition or overnutrition. The knowledge of parents, especially mothers, about eating patterns greatly influences nutritional status. This research aims to determine the relationship between the level of maternal knowledge and children's eating patterns with children's nutritional status among students at SDN 14 Way Serdang. This research was carried out using a quantitative, analytical observational approach with a cross sectional approach design. The population of this study was all class III students at SDN 14 Way Serdang with a sample of 61 people. This research instrument for maternal knowledge uses a nutritional knowledge questionnaire in the form of 20 questions, eating patterns using a food frequency questionnaire (FFQ), and nutritional status using scales and micrometers. Univariate and bivariate data analysis using the chi-square test. The results of this study showed that of the 61 samples there were 31.0% overeating patterns, 36.0% of respondents with insufficient knowledge, and 28.0% of respondents with excess nutritional status. The results of the chi-square test showed that there was a relationship between mother's knowledge and the child's nutritional status (p=0.001), there was a relationship between the child's diet and the child's nutritional status (p=0.001). Based on this research, it is hoped that mothers will pay more attention to their children's diet in order to achieve normal nutritional status for their children.